Job satisfaction level of teachers in Dueñas General Comprehensive High School, Dueñas, Iloilo. - Dawatan, Melanie Laguerta (1996.)
The purpose of this study was to determine the general level of satisfaction of the teachers in the nature of work, supervision, interpersonal relationships to their age and lenght of service. The respondents of the study were the 41 faculty members of the school. The instrument used in data gathering is the Job Descriptive Index. Simple frequency, percentages, Pearson Moment Correlation Coefficient and test were used, at the 0.05 level of significance., The findings of the study reveal that there is no significant relationship between the level of satisfaction of the teachers in the nature of work, interpersonal relationships, pay and promotion and the age of the teachers. Similar results were found when these job aspects were correlated to their lenght of service. Only supervision was found to have a significant correlation with their age and lenght of service. The teachers have a very high level of satisfaction in the supervision aspect of their jobs and less satisfied with their salary. This research recommends providing opportunities for advancement of the teachers and more studies should be conducted on the evaluation of the teachers' salary. It is also recommended that more studies should be conducted on other factors that affects the level of satisfaction of the teachers like the demographic variables not covered in this study.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Teachers -- Duenas, Iloilo